Harnessing Sentiment Analysis Methodologies for Business Intelligence Enhancement and Governance Intelligence Evaluation - Sinha, Sourav; Narayanan, Revathi Sathiya; Rakila, Rakila (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The growing popularity of the electronic regime insisted on a larger number of individuals sharing their feelings through different forums.in social media. In today’s business world interaction and correspondence through media have become part and parcel of the exchange of views and opinions between individual and mass communications. Consumers share their experiences with reviews; moviegoers give their comments on films while tourists express their hotel views. One thing that is common among them is to deliberate respective sentiments on the concerned issues. Several thousands of people deliver their sentimental outbursts in a day. The collective sentiment of such a huge volume of review comments needs an effective mechanism to be addressed. Sentiment analysis is the state-of-the-art process that helps in evaluating opinions and expressions. In this paper; the components of sentiment analysis are covered with three subprocesses namely feature extraction, methodologies and evaluation performed in the process of sentiment analysis. We also discuss applications of sentiment analysis in the areas of business intelligence, recommendation systems, governance intelligence and review summarization.